The European human biomonitoring platform - Design and implementation of a laboratory quality assurance/quality control (QA/QC) programme for selected priority chemicals - Esteban López, Marta; Göen, Thomas; Mol, Hans; Nübler, Stefanie; Haji-Abbas-Zarrabi, Karin; Koch, Holger M; Kasper-Sonnenberg, Monika; Dvorakova, Darina; Hajslova, Jana; Antignac, Jean-Philippe; Vaccher, Vincent; Elbers, Ingrid; et al. (International journal of hygiene and environmental health, 2021)
A fundamental objective of the human biomonitoring for Europe initiative (HBM4EU) is to progress toward comparable and robust exposure data for a wide variety of prioritized chemicals in human samples. A programme for Quality Assurance/Quality Control (QA/QC) was designed in HBM4EU with the purpose of creating a network of European laboratories providing comparable analytical data of high quality. Two approaches were chosen for two sets of prioritized chemicals with different timelines: (i) Scheme 1, where interested candidate laboratories participated in multiple rounds of proficiency tests (ii) Scheme 2, where selected expert laboratories participated in three rounds of interlaboratory comparison investigations. In both cases, the results were used to identify laboratories capable of generating consistent and comparable results for sample analysis in the frame of HBM4EU. In total, 84 laboratories from 26 countries were invited to participate in Scheme 1 that covered up to 73 biomarkers from Hexamoll® DINCH, phthalates, bisphenols, per- and polyfluoroalkyl substances, halogenated flame retardants (HFRs), organophosporous flame retardants (OPFRs), polycyclic aromatic hydrocarbons (PAH), cadmium, chromium and aromatic amines. 74 of the participants were successful for at least one biomarker in Scheme 1. Scheme 2 involved 22 biomarkers and successful results were obtained by 2 expert laboratories for arsenic, 5 for acrylamide, 4 for mycotoxins, 2 for pesticides and 2 for UV-filters in skin care products. The QA/QC programme allowed the identification of major difficulties and needs in HBM analysis as well of gaining insight in the analytical capacities of European laboratories. Furthermore, it is the first step towards the establishment of a sustainable European network of HBM laboratories.
Keywords: laboratoře; monitorování životního prostředí; biologický monitoring; Humans; Quality Control; External; pesticidy; HBM4EU; Laboratories; lidé; Quality assurance scheme (EQUAS); Interlaboratory comparison investigation (ICI); Biological Monitoring; Pesticides; Human biomonitoring (HBM); Environmental Monitoring; řízení kvality